PERSONALITY MOVEMENT OF MAIN CHARACTER IN LADY BIRD MOVIE DIRECTED BY GRETA GERWIG - arfani, Sri; Kameswari, Agung Ayu (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
Movie has been developing since the 18th century, from just a moving picture until a very big production that includes many things such as camera, microphone, even a computer for adding the effects or additional sounds to the movie. Lady Bird (2017) is one of the greatest movies according to the writer, it has a unique aspect from the main character, Christine McPherson, a teenager who lives in Sacramento, U.S. Christine does not want people to call her by her name, but Lady Bird instead. The fact that Christine eventually gives up on making her life up and trying to live her life normally as she should, interests the writer to discuss Christine’s character development. The writer thinks about what Christine McPherson did in the movie is extraordinarily amazing. She changed from a girl that likes to make something up into a girl that accept everything that happens in her life.